The Reliability of the Wall Drop Punt Kick and Catch Test - Matos, Rui (2023)
This study aimed to evaluate the reliability of a manipulative eye–segmental (hand and foot) coordination task, namely the Wall Drop Punt Kick and Catch test (WDPK&C), over two weeks. Forty-one children and adolescents (18 boys, 23 girls) with a mean age of 10.2 (SD =1.62) years old were recruited for assessment. Subjects had 30 s to perform as many ball impacts as possible on a wall two meters away, following a drop punt kick, rebound on the wall, and catch sequence. The Intraclass Correlation Coefficient (ICC = 0.896) for unique measures, Cronbach Alpha (α = 0.945), and Lin’s Concordance Correlation Coefficient (CCC = 0.896) provide evidence of reliability considering two consecutive measurements. These results further support the reliability of the WDPK&C test in a sample of Portuguese children and adolescents. Thus, the WDPK&C test can be applied to Portuguese boy and girl children and adolescents. Forthcoming studies should test the reliability of this test across different age groups since it is intended to be a test with a wide lifespan coverage.